Merdeka Belajar Curriculum Policy Implementation: A Study of Teacher’s Perceptions in Senior High Schools of Konawe Regency - Samrin, Samrin; Alimuna, Wa; Awan, Rusdi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study is a qualitative descriptive research aimed at understanding teachers' perceptions of the